2019
DOI: 10.1590/0104-1428.02518
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility and characterization of Bio-PE/PCL blends

Abstract: In this work, blends based on environmentally friend polymers such as Biopolyethylene (Bio-PE), Polycaprolactone (PCL) and Polyethylene graft maleic anhydride (PEgMA) added as compatibilizer agent were produced by conventional extrusion, aiming to produce bio-blends with synergic properties at low processing cost, being at same time non-polluting and therefore contributing to the environment preservation. Differential scanning calorimetry (DSC) showed that blending does not significantly interfere on the melti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 38 publications
1
7
0
2
Order By: Relevance
“…Figure 10 shows the results of the heat de ection temperature of BioPE and composites, with and without macaíba oil, respectively. It is observed that the HDT value for BioPE was 70.3°C, value close of the literature [65].…”
Section: Heat De Ection Temperature (Hdt)supporting
confidence: 87%
“…Figure 10 shows the results of the heat de ection temperature of BioPE and composites, with and without macaíba oil, respectively. It is observed that the HDT value for BioPE was 70.3°C, value close of the literature [65].…”
Section: Heat De Ection Temperature (Hdt)supporting
confidence: 87%
“…Poly(ε-caprolactone) (PCL) is a chemically synthesized polymer which is fully biodegradable and can be processed using conventional plastics machinery [ 29 ]. Moreover, it has good properties and is also compatible with other materials [ 30 ]. Regarding the use of PCL for active packaging applications, Khalid et al [ 31 ] developed biodegradable antimicrobial packaging films based on PCL, starch and pomegranate rind hybrids showing a strong antimicrobial efficiency at higher concentrations of the active compound.…”
Section: Introductionmentioning
confidence: 99%
“…According Bezerra et al, the addition of Bio‐PE to PCL reduced the elastic modulus, increased the elongation at break and impact strength, allowing a control of these properties by changing the blend composition. PCL chains when oxidized exhibited new functional groups (vinyl and hydroxyl) and possible intermolecular recombination, producing an oxidized‐polycaprolactone (PCL‐OX) 81 . The blend prepared with oxidized PCL (in the same composition range) did not display signs of thermodynamic miscibility but showed an interesting thermal behaviour demonstrated by changes in the crystallization temperatures of both phases and by the melting behaviour of the PCL‐OX in the blend.…”
Section: Pcl Compatibility With Other Polymersmentioning
confidence: 99%